Improvement of The Activities of Student Services at University North, University Center Varaždin (Vallis Aurea, 2016)
An organization is a group of people who enable the achievement of a common goal using their own efforts. Organizing is a process which has two specific parts: the structure of a company and coordination of human resources. They are both very important and almost indispensable in business economics and the modern business world. Therefore, in the context of this definition, University North is seen as an organizational unit with all its features, i.e. advantages and problems. An organization (manufacturing or service) cannot be imagined and cannot operate or survive in the market unless proper, timely and quality selection of the organizational structure together with its maintenance and improvement are taken into account. Having that in mind, certain problems have been noticed in the organization of University North which hamper its effectiveness. Student services, as one of the organizational units, contribute to its work and it is very important for the total satisfaction of the most important subjects – students, as well as teachers and other interested parties. Based on many years of work in student services and previous knowledge, it has been noticed that the effectiveness of tasks carried out by the student services is not at the expected and required level, i.e. it is possible to increase their efficiency to a higher level by reorganization and certain improvements. The efficiency and effectiveness of student services is determined by the satisfaction of students and all other stakeholders – teachers, workers, graduates, employers, associates, and others. The paper presents an analysis and research of a better organization with the purpose of improving the organization and efficiency of the Student Services at University North. Upon recognizing and defining the problems for this research, the data have been collected in order to get an insight into the current situation, which is generally defined by the hypotheses. Using surveys, this research examines the students’ satisfaction/dissatisfaction regarding the services provided by the Student Services on a daily basis. Do students of University North consider that this unit provides quality services and is available to them? Upon collecting the data, an analysis has been conducted, i.e. the situation has been studied so as to find propositions for improvement. Various tools and methods were used in that part of the paper in order to enable the observation of the optimum alternative to the solution. The research results will serve as indicators of how to increase the student satisfaction with regard to the work of the Student Services and how to improve their efficiency.